Studies on physico-chemical and biological parameters of Chorgaon Lake Distt. Chandrapur, India - P.M. Telkhede; N.R. Dahegaonkar; S.B. Zade; C. J. Khune; A.N. Lonkar (Environment Conservation Journal, 2008)
Chorgaon lake  is  a  man  made  fresh water reservoir at Chorgaon village, in  Distt.   Candrapur. The  present study has  been  made to  investigate the  physico-chemical and  biological status of  the  lake.  The  study  involves the   physico-chemical analysis  like  DO,  COD,   BOD, Alkalinity,  Total  Hardness,  Chloride, Sulphate and  Phosphate along   with other parameters  and   quantitative and   qualitative  analysis of phytoplankton and zooplankton  in  biological parameters.  Samples were  collected from  four sampling stations of the  lake.The results revealed that  site  S,  and  S, shows more Nitrogen  and  Phosphate, which   favoured the  growth of phytoplankton  and  zooplankton.  Phytoplankton  shows  dominance of  Bacillariophyceae. In  zooplankton abundance of  Rotifers,  Cladocerons & Copepods  were observed. The  average value   revealed that  Dioptomus shows   dominance in  zooplankton and  Diatoms  in  phytoplankton. At other sites   parameters  remained in constant range  showing no  much  variation thus   indicating better  quality of  water, which   was  free  from pollution